Trip generation modeling in the residential areas of downtown Cagayan de Oro City, Misamis Oriental, Philippines - Edulan, Chris Lawrence O. (Journal in Urban and Regional Planning, 2017)
Access online through this link: https://journals.upd.edu.ph/index.php/SURP/article/view/8932/7881